Challenges for intraventricular hemorrhage research and emerging therapeutic targets - Garton, Thomas (Expert Opin Ther Targets, 2017)
INTRODUCTION –: Intraventricular hemorrhage (IVH) affects both premature infants and adults. In both demographics, it has high mortality and morbidity. There is no FDA approved therapy that improves neurological outcome in either population highlighting the need for additional focus on therapeutic targets and treatments emerging from preclinical studies. AREAS COVERED –: IVH induces both initial injury linked to the physical effects of the blood (mass effect) and secondary injury linked to the brain response to the hemorrhage. Preclinical studies have identified multiple secondary injury mechanisms following IVH, and particularly the role of blood components (e.g. hemoglobin, iron, thrombin). This review, with an emphasis on pre-clinical IVH research, highlights therapeutic targets and treatments that may be of use in prevention, acute care, or repair of damage. EXPERT OPINION –: An IVH is a potentially devastating event. Progress has been made in elucidating injury mechanisms, but this has still to translate to the clinic. Some pathways involved in injury also have beneficial effects (coagulation cascade/inflammation). A greater understanding of the downstream pathways involved in those pathways may allow therapeutic development. Iron chelation (deferoxamine) is in clinical trial for intracerebral hemorrhage and preclinical data suggest it may be a potential treatment for IVH.